Association of Obstructive Sleep Apnea With Nighttime Blood Pressure in African Americans: The Jackson Heart Study. (3rd June 2020) - Thomas, Stephen Justin; Johnson, Dayna A; Guo, Na; Abdalla, Marwah; Booth, John N; Spruill, Tanya M; Jackson, Chandra L; Yano, Yuichiro; Sims, Mario; Calhoun, David; Muntner, Paul; Redline, Susan
Abstract: BACKGROUND: Obstructive sleep apnea (OSA), nocturnal hypertension, and nondipping systolic blood pressure (BP) are each highly prevalent among African Americans. However, few data are available on the association between OSA and nighttime BP in this population. METHODS: We examined the association of OSA with nighttime BP among African Americans who completed 24-hour ambulatory BP monitoring (ABPM) at Exam 1 (2000–2004) of the Jackson Heart Study (JHS) and subsequently participated in the JHS Sleep Study (2012–2016). Type 3 home sleep apnea testing was used to assess OSA measures, including respiratory event index (REI4%) and percent sleep time <90% oxygen saturation (nocturnal hypoxemia). Nocturnal hypertension was defined as mean asleep systolic BP (SBP) ≥120 mm Hg or diastolic BP (DBP) ≥70 mm Hg. Multivariable linear regression models were fit to estimate the association between each OSA measure and nighttime SBP and DBP. RESULTS: Among 206 participants who completed ABPM and participated in the Jackson Heart Sleep Study, 50.5% had nocturnal hypertension and 26.2% had moderate to severe OSA (REI4% ≥15 events/hour). After multivariable adjustment, each SD (13.3 events/hour) increase in REI4% was associated with 1.75 mm Hg higher nighttime DBP (95% confidence interval (CI): 0.38, 3.11) and a prevalence ratio of 1.11 (95% CI: 1.00, 1.24) for nocturnal hypertension. Each SD (10.4%) increase in nocturnal hypoxemia was associated with a 1.91 mm Hg higher nighttime SBP (95% CI: 0.15, 3.66). CONCLUSIONS: Severity of OSA and nocturnal hypoxemia were associated with high nighttime BP in African American participants in the JHS.